KESIAPAN SISWA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI3 PAYAKUMBUH DALAM MELAKSANAKAN PRAKTEK KERJA INDUSTRI (PRAKERIN) DI SALON KECANTIKAN - Yolanda, Siska Septia; Hayatunnufus, Hayatunnufus; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
following industry practice. It can be seen from the students' lack of knowledge related to the subjects of productive, affective, and psychomotor. This study aims to disclose a student's readiness skills skin competency and hair beauty in SMK 3 Payakumbuh.The research is a descriptive quantitative research, and the population in this study was a class XI student competency skills hairstyling and skin care procedures, amounting to 46 people and everyone is included in the sample (total sampling). Data collection techniques for data cognitive and affective are using questionnaires as well as the documentation of learning outcomes for the data subject teachers psychomotor.The results of this study indicates that student's readiness is low with the level of achievement of 50% of respondents in skin care system, 67% category is for students hairstyling. For both affective readiness classes are included the percentage score of 60% with a low category while for readiness skills (psychomotor) for skin care system students there are 14 people (58%) of students who did not complete the KKM and for hairdressing students there are 11 people (50%) KKM incomplete. Therefore, to support a student's readiness skills competency skin and hair beauty procedures required readiness of cognitive, affective, psychomotor order to support the activities of prakerin.Keywords: Student Readiness, industry practices.